Development of Friendship and Task Values in a New School: Friend Selection for the Arts and Physical Education but Socialization for Academic Subjects - Chow, Angela; Kiuru, Noona; Parker, Philip D.; Eccles, Jacquelynne S.; Salmela-Aro, Katariina (Journal of youth and adolescence, 2018)
Friends provide important social contexts for student development. Research has shown that adolescent friends are similar to each other in their interest and values for different school subjects. Yet our current understanding does not extend to knowing whether selection, deselection, or socialization processes are responsible for this phenomena. Without this knowledge, it is very difficult for parents, teachers, and schools to know how and when to intervene. This study investigated selection, deselection, and socialization effects on adolescent students’ task values for academic (languages, math and science, and social sciences) and non-academic subject areas (the arts and physical education). A social network approach was used to examine two waves of annual data collected from school-based networks of adolescents in the first and second years of high school education in Finland ( N = 1419; female = 48.6%; mean age at first measurement point = 16). The results revealed that adolescents tended to select friends with similar levels of task values ( friend selection ) for the arts and physical education, but friends did not become more similar in these areas over time ( friend socialization ). In contrast, there was evidence of friend socialization, but not friend selection, for the academic school subjects. Across all subjects, differences in task values did not predict friendship dissolution ( friend deselection ). These findings suggest that to a significant extent, students make agentic choices in developing friendship with schoolmates based on their task values in non-academic subjects. The resultant friend contexts that individuals created, in turn, affected their task values in academic subject areas. These results shed light on the complexity of friend effect mechanisms on task values at the subject domain-specific level.